(untitled) (Journal of Oriental Studies, 2016)
This article consider the stylistic features of quantitative words in Chinese language. The main feature of the Chinese language is the presence of quantitative words and their wide usage. It is one of the challenging problems in teaching students Chinese language. Peculiarity of characteristics of quantity words in the Chinese language is not only a grammatical, but semantic and pragmatic. In this article, along with listing the main problems also was made stylistic analysis of quantitative words.